RELEVANCE OF KUNTOWIJOYO'S PROFETIC SOCIAL SCIENCE WITH ARIF MAFTUHIN'S “BEYOND THE RUKHSAH” IDEA - Awalluddin, Awalluddin (Madura State Islamic Institute (Institut Agama Islam Negeri (IAIN) Madura), 2025)
ABSTRACT Contemporary social problems require an integrative approach from various academic disciplines to achieve meaningful transformative solutions. This research aims to analyze the relevance of Kuntowijoyo's